An Expeditious Synthesis of cis-2-(Aroylmethyl)-4-phenylthiochromans by Iodine-Catalyzed Combination of Thiophenol with Cinnamylideneacetophenones - Mallik, Asok K.; Mandal, Tapas K.; Pal, Rammohan; Ghosal, Debojyoti; Patra, Amarendra (Synlett, 2012)
Cinnamylideneacetophenones have been found to undergo facile cyclocondensation with thiophenol in dichloromethane under iodine-catalyzed conditions yielding cis-2-(aroylmethyl)-4-phenylthiochromans in very good to excellent yield. The structures of the products have been established from their spectral data as well as X-ray crystallographic studies on one of them.
Keywords: thiophenol; cinnamylideneacetophenones; iodine; cis-2-(aroylmethyl)-4-phenylthiochromans